2021
DOI: 10.1016/j.ijplas.2021.102936
|View full text |Cite
|
Sign up to set email alerts
|

Single layer graphene controlled surface and bulk indentation plasticity in copper

Abstract: The impact of graphene reinforcement on the mechanical properties of metals has been a subject of investigation over the last decade in surface applications to mitigate the impact of tribological loadings or for strengthening purposes when dispersed into a bulk material. Here, the effect on the plastic indentation response of a single graphene layer grown on Cu is analyzed for two configurations: one with graphene at the surface, the other with graphene sandwiched under a 100 nm thick Cu cap layer.Nanoindentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…They showed that the experimentally observed effects could be rationalized based on the large back-stress induced by the graphene layer that acts as an impermeable barrier and leads to the delocalization of plasticity events. While these results agree with the ones presented in Reference [20], the authors in Reference [21] also found that the onset of plastic deformation of copper occurs at a lower load level in the presence of a graphene monolayer. This is in contrast to results in References [19,20].…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…They showed that the experimentally observed effects could be rationalized based on the large back-stress induced by the graphene layer that acts as an impermeable barrier and leads to the delocalization of plasticity events. While these results agree with the ones presented in Reference [20], the authors in Reference [21] also found that the onset of plastic deformation of copper occurs at a lower load level in the presence of a graphene monolayer. This is in contrast to results in References [19,20].…”
Section: Introductionsupporting
confidence: 92%
“…There, sudden jumps in the friction force signal were observed upon graphene rupture that was preceded by plasticity events in underlying platinum. The load-carrying effect of graphene grown on copper has further been simulated and measured during nanoindentation experiments [20,21]. In Reference [20], the authors performed molecular dynamic simulations of nanoindentation to better understand the effects of graphene on the plastic deformation of copper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene has been used to improve tribological property due to its extraordinary properties [18][19][20]. Graphene oxide (GO) is considered as a promising material for reducing friction and wear, owing to its structural features [21].…”
Section: Coating Materialsmentioning
confidence: 99%
“…29,30 So far, the mechanical behaviour of graphene mounted on various substrates has been widely investigated using nanoindentation experiments and simulations. [31][32][33][34][35][36][37] The results have shown that the interaction between graphene and the substrate can greatly affect the mechanical properties of graphene and its applications. Thus, it is reasonable to expect that the substrate may similarly have an impact on the mechanical behaviour and failure mechanisms of supported MoS 2 .…”
Section: Introductionmentioning
confidence: 99%